Mowa w zaniku wieloukładowym – problem diagnozy logopedycznej. Studium przypadku - Sochacka, Justyna (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The article describes some relations between the central nervous system and language usage by a multiple system atrophy patient. It shows some complex sources of speech processes found in multiple system atrophy in reference to speaking without any disorders. It characterises some speech disorders and term them. This article emphasises a great importance of diagnosis of speech defects and shows some steps made by the author in a complex diagnostic process. The article doesn’t ignore some theoretical issues based on the results presented by speech therapists, podiatrists, neurologists, otolaryngologists over the years.